Microencapsulation of Acetaminophen and in vitro dissolution studies - Bykadi, Gururaj
This work was undertaken to develop a process of microencapsulation of Acetaminophen by a simple coacervation method and to evaluate several of the variables affecting their formation. Acetaminophen microcapsules were prepared by simple coacervation of cellulose acetate phthalate with sodium sulfate at a temperature of 60(degrees C). In vitro dissolution studies were performed on acetaminophen microcapsules in 0.1N HCl dissolution media and an evaluation was made of their release characteristics. It was observed that microencapsulation of acetaminophen can be accomplished by a simple coacervation process employing 58% w/w cellulose acetate phthalate as encapsulating agent and 18 ml of sodium sulfate (20% w/w) as coacervating agent at a temperature of 60(degrees C). The in vitro dissolution studies performed on the acetaminophen microcapsules showed that there was an initial rapid release of drug within a period of 5-10 minutes with the remaining drug being released gradually over a period of 150 minutes. The initial rapid release of the drug may be due to some unencapsulated acetaminophen present in the microcapsules. When dissolution studies were performed in 0.1M phosphate buffer (pH 7.5), the release of drug from the microcapsules was complete within 10 minutes.
Formulations prepared from microencapsulated acetaminophen in the form of pellets and tablets showed a gradual release of 80-90% of the drug over a period of 48 hours in 0.1N HCl dissolution media. The release of drug from tablets prepared from microencapsulated acetaminophen in 0.1M phosphate buffer was found to be shorter in duration as compared to the release of drug from similar tablets in 0.1N HCl dissolution media. This was probably due to solubility differences of the coating material used for encapsulation of acetaminophen. Release data were analyzed using a "NONLIN" computer program to determine the best polyexponential fit. The results indicated a single exponential equation for uncapsulated material and a biexponential equation for macroencapsulated materials which may be used to describe the release profiles. The release pattern of drug from microcapsules and the formulation prepared from them was observed to occur by a diffusion process analogous to the diffusion of material out of an insoluble porous matrix.
Available to the general public.
Thesis (Doctor of Philosophy in Pharmaceutics)--University of Mississippi, August 1978.
Keywords: Microencapsulation; Acetaminophen